Primary unilateral cleft lip nasal deformity repair using V-Y-Z plasty: An anthropometric study - Rossell-Perry, Percy (2017)
Background: Secondary nose deformity after unilateral cleft lip repair is a common problem. Loss of tip projection on the cleft side of unilateral cleft lip nasal deformity can be difficult to correct due to lack of adequate support. The purpose of this study is to evaluate the surgical outcome after using V-Y-Z plasty to address unilateral cleft lip nasal deformities. Methods: A cross-sectional study of one surgeon's outcome of 58 performed primary complete unilateral cleft lip nasal deformity repairs. All these patients met the study criterion of having anthropometric measurements at the cleft and non-cleft side of the nose performed at least 1 year postoperatively. Results: Since 2012, 32 consecutive patients have undergone primary anatomical repair of the cleft nasal deformity in patients with a complete unilateral cleft. We have not found statistically significant differences between the cleft and non-cleft nostril dome height and columella length measured at least 1 year postoperatively. Conclusions: The findings suggest that the V-Y-Z plasty is a good alternative to create a more symmetric nasal tip in patients with primary unilateral cleft lip nasal deformity. Additional studies are required to evaluate functional and long-term outcomes after primary rhinoplasty in patients with unilateral cleft lip.